Community-acquired pneumonia: doctors do not follow national guidelines. Issue 982 (3rd August 2007) - Collini, Paul; Beadsworth, Mike; Anson, Jim; Neal, Tim; Burnham, Peter; Deegan, Paul; Beeching, Nick; Miller, Alastair
Abstract : Objectives: Appropriate assessment of community-acquired pneumonia (CAP) allows accurate severity scoring and hence optimal management, leading to reduced morbidity and mortality. British Thoracic Society (BTS) guidelines provide an appropriate score. Adherence to BTS guidelines was assessed in our medical assessment unit (MAU) in 2001/2 and again in 2005/6, 3 years after introducing an educational programme. Methods: A retrospective case-note study, comparing diagnosis, documentation of severity, management and outcome of CAP during admission to MAU during 3 months of each winter in 2001/2 and 2005/6. Results: In 2001/2, 65/165 patients were wrongly coded as CAP and 100 were included in the study. In 2005/6 43/130 were excluded and 87 enrolled. In 2005/6, 87% did not receive a severity score, a significant increase from 48% in 2001/2 (p<0.0001). Parenteral antibiotics were given to 79% of patients in 2001/2 and 77% in 2005/6, and third generation cephalosporins were given to 63% in 2001/2 and 54% in 2005/6 (p = NS). In 2001, 15 different antibiotic regimens were prescribed, increasing to 19 in 2005/6. Conclusions: Coding remains poor. Adherence to CAP management guidelines was poor and has significantly worsened. Educational programmes, alone, do not improve adherence. Restriction of antibiotic prescribing should be considered.